2021
DOI: 10.1016/j.heliyon.2021.e06843
|View full text |Cite
|
Sign up to set email alerts
|

Depth estimates of anomalous subsurface sources using 2D/3D modeling of potential field data: implications for groundwater dynamics in the Ziway-Shala Lakes Basin, Central Main Ethiopian Rift

Abstract: Quantitative analysis of potential field data are made in the Ziway-Shala lakes basin over an area bounded by 38 ° 00′ E - 39 ° 30′ E and 7 ° 00′ N - 8 ° 30’ N. Most previous geophysical studies in the region under consideration focus on mapping the deep crustal structures and undulation of the Moho depth. Only few studies are targeted at mapping the shallow subsurface structures. The main focus of this paper is mapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…A total of about 2335 secondary including primary total magnetic intensity (TMI) data are used to compute the CPD beneath the central MER and surrounding regions. The secondary TMI data were obtained from MSc works of numerous scholars (Kebede, 2014; Berhane 2015 ; Kelemework, 2016 ; Nigussie, 2020 ) and Kebede et al. (2021) guided by their advisor Dr. Abera Alemu.…”
Section: Methodsmentioning
confidence: 99%
“…A total of about 2335 secondary including primary total magnetic intensity (TMI) data are used to compute the CPD beneath the central MER and surrounding regions. The secondary TMI data were obtained from MSc works of numerous scholars (Kebede, 2014; Berhane 2015 ; Kelemework, 2016 ; Nigussie, 2020 ) and Kebede et al. (2021) guided by their advisor Dr. Abera Alemu.…”
Section: Methodsmentioning
confidence: 99%
“…Field studies showed that in some localities of Amaro Horst crystalline basement is unconformably overlain by Pre-Tertiary or Mesozoic sedimentary rocks possibly extend into studied sub-basins with larger thickness than the elevated area where the unit is exposed. Multi-Layer 3D gravity forward modeling in northern parts of Ethiopia by Mammo (2010) and 2D/3D modeling of potential field data in Central MER by Kebede et al. (2021) shows that the existence of Mesozoic sediment overlaid on the Precambrian basement rock.…”
Section: Resultsmentioning
confidence: 97%
“…The NNE-SSW trending regional rift forming faults are also observed on Southern MER (B. Kebede & Mammo, 2021;H. Kebede et al, 2021).…”
Section: Geological Setting Of the Study Areamentioning
confidence: 86%